Evaluation of Peat Nutrient Content in Coconut Plantations: Palm oil (Elaeis gueneensis Jacq.) In Paham Labuhanbatu - Munawarah; T. Irmansyah; Abdul Rauf (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The use of peatlands for oil palm cultivation involves soil processing techniques, including physical soil improvement and water management, which can alter groundwater levels. These processes can change the peat structure from coarse to very soft and compact, ultimately affecting its chemical properties. This study aims to evaluate the nutrient content of peat at different depths in oil palm plantations. A descriptive method was employed by collecting soil samples from degraded areas at depths of 0–30 cm (top layer) and 30–60 cm (bottom layer). Observations were conducted over several years of oil palm cultivation. The results indicate that at 0–30 cm depth, total nitrogen (N) and potassium oxide (K₂O) content tended to be higher in 2015, whereas phosphorus pentoxide (P₂O₅) content was higher in 2013. In conclusion, variations in planting years suggest an interaction between plant age and nutrient content in peat. This finding underscores the importance of considering soil depth and plant age to maintain peat soil fertility in oil palm plantations. Consequently, fertilization and land management strategies can be implemented more efficiently and sustainably.